Monosynaptic trans-collicular pathways for sensory-motor integration in the whisker system [research data] - Martín-Cortecero, Jesús; Isaías-Camacho, Emilio Ulises; Boztepe, Berin; Ziegler, Katharina; Mease, Rebecca A.; Groh, Alexander (Universität, 2023)
This dataset contains electrophysiological spike time data and figure data for anatomical quantifications reported in Martín-Cortecero et al. Monos...